The effects of parental involvement on children’s education: a study in elementary schools in Indonesia - Yulianti, Kartika; Denessen, Eddie; Droop, Mienke (International Journal about Parents in Education, 2023)
The Indonesian government through the Ministry of Education has begun to emphasize the importance of parental involvement and community participation in children’s education. However, there is a lack of research on parental involvement in Indonesia. The aim of the study is to provide insights into parental involvement in children’s education in urban and rural areas in Java, Indonesia. The sample comprised 2151 second to sixth graders in 18 schools in three regions, DKI Jakarta, West Java, and East Java. Six aspects of parental involvement were measured using an adapted version of Epstein’s parental involvement framework. Hierarchical regression analyses were conducted to examine the effects of the socioeconomic and demographic characteristics and different types of parental involvement on children’s academic achievements as measured by the most recent Indonesian language and Mathematics grades. The finding shows that Indonesian parents are more strongly involved in their children’s learning at home than at school. Parents show higher levels of involvement when mothers had higher levels of education, in particular with respect to parenting, communicating, volunteering, and learning at home. With regards to school settings, parents in urban schools show higher levels of involvement than parents in rural schools. In urban schools, highly educated parents were more involved in volunteering, decision making and collaborating with community than low educated parents. In contrast to urban schools, in the rural school setting, parents with low education show higher involvement than their highly educated counterparts. Volunteering and learning at home have small positive effects on students’ mathematics achievement. Parenting and learning at home show small positive effects on students’ Indonesian language achievement.